Angiotensin‐converting enzyme insertion/deletion gene polymorphism in Egyptian children with CAP: A case‐control study. Issue 12 (13th October 2017) - Abouzeid, Heba; Alkholy, Usama M.; Abdou, Mohammed A.; Morsy, Saeed M.; Abdelrahman, Hind M.; Sherif, Ashraf M.; Abdalmonem, Nermin; Hamed, Mohammed E.; Allah, Mayy A.N.; Al Morshedy, Salah; Elashkar, Shaimaa S.A.; Noah, Maha A.; et al.
Abstract: Background: Community‐acquired pneumonia (CAP) is a major cause of childhood morbidity and mortality worldwide. The angiotensin‐converting enzyme ( ACE ) gene is a potential candidate gene for CAP risk. Objectives: In this study, we aimed to investigate whether the ACE insertion/deletion (I/D) polymorphism (rs4340) could be a genetic marker for CAP susceptibility in Egyptian children, and we also measured the serum ACE level to assess its relation to such polymorphism. Methods: This was a prospective case‐control study included 300 patients with CAP, and 300 age, gender, and ethnicity matched healthy controls. The ACE I/D polymorphism (rs4340) at intron 16 was genotyped by polymerase chain reaction‐restriction fragment length polymorphism ( PCR‐RFLP ), while the serum ACE levels were measured by ELISA . Results: Compared to the controls subjects, the frequencies of the ACE DD genotype and D allele were overrepresented in patients with CAP (OR = 3.05; [95%CI: 2.14‐4.35] for the DD genotype; P < 0.001) and (OR: 1.8; [95%CI: 1.42‐2.29]; for the D allele; P < 0.01, respectively). Patients with the DD genotype had significantly higher mean serum ACE levels (45.6 ± 11.4 U/L) compared to those with ID genotype (36.5 ± 8.3 U/L) and II genotype (21.6 ± 5.7 U/L); P < 0.01, respectively. Conclusion: The ACE I/D polymorphism (rs4340) may contribute to the genetic susceptibility of CAP in Egyptian children. The ACE D allele and DD genotype were associated with higher serum ACE levels among studied CAP patients.